PERSEKUTUAN PERDATA MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS DAN KITAB UNDANG-UNDANG HUKUM PERDATA TERHADAP PRINSIP KEMANDIRIAN NOTARIS - Zimri Boy Yoyada Sinuhaji (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract Civil partnership as stated in Civil Code is defined as an agreement that bind the parties to enclose certain thing into partnership in order to gain the expected profit. The form of civil partnership is the corporation and it often aims to share the obtained profit. However, UUJN No.2/2014 does not clearly explain civil partnership. Notary civil partnership can be arranged by Notary based on stipulations of certain law. Indeed, the law that regulates civil partnership is Civil Code. Notary is the public officer who is required to be independent in performing the task. The objective of this research is to examine civil partnership based on UUJN No.2/2014 and Civil Code and also to review the independence principle of Notary in performing the task. Method of research is normative. The theory used to analyze the problem, whether civil partnership in Article 20 Law No.2/2014 about the amendment of Law No.30/2004 has allowed Notary to establish corporation with other parties by the goal of obtaining profit while still performing the job as Notary, is theory of norm stratification. Based on the result of discussion, it can be said that civil partnership stated in Article 20 UUJN No.2/2014 has indeed allowed Notary to establish corporation with other parties to obtain profit because there is no further explanation about Notary civil partnership in Article 20 UUJN No.2/2014 such that stipulations inside Civil Code are considered as supporting the establishment of Notary civil partnership. The theory to analyze problem, whether after establishing civil partnership, Notary still can maintain independence principle in their job implementation, is theory of accountability. Result of discussion indicates that Notary independence in preparing the certificate of civil partnership is still persistent because Notary is always subjected to the accountability as certificate maker. However, Notary independence can be distorted because the cooperation in civil partnership may involve many alliances and thus, Notary cannot be standalone or independent in term of financing. Key words: notary civil partnership, notary independence principle Abstrak Persekutuan perdata menurut KUHPer merupakan badan usaha dan bertujuan untuk membagi keuntungan sedangkan persekutuan perdata menurut UUJN No. 2 Tahun 2014 tidak dijelaskan lebih lanjut. Persekutuan perdata diatur oleh Notaris menurut ketentuan peraturan perundang-undangan. Peraturan perundang-undangan tentang persekutuan perdata adalah KUHPer. Notaris mempunyai kewajiban untuk mandiri dalam menjalankan jabatan. Penelitian ini bertujuan mengkaji persekutuan perdata menurut UUJN No. 2 Tahun 2014 dan KUHPer dan prinsip kemandirian Notaris yang wajib dipertahankan dalam menjalankan jabatan. Metode yang digunakan adalah metode normatif. Teori yang digunakan dalam menganalisa rumusan masalah apakah persekutuan perdata menurut pasal 20 Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 memperbolehkan Notaris membentuk badan usaha secara bersama-sama dengan maksud memperoleh keuntungan dalam menjalankan jabatan sebagai Notaris sesuai dengan KUHPer adalah dengan menggunakan teori penjenjangan norma. Berdasarkan hasil pembahasan Persekutuan perdata menurut UUJN No. 2 Tahun 2014 memperbolehkan Notaris membentuk badan usaha secara bersama-sama dengan maksud memperoleh keuntungan karena tidak terdapat penjelasan lebih lanjut mengenai persekutuan perdata Notaris dalam UUJN No. 2 TAHUN 2014 sehingga KUHPer yang berlaku terhadap persekutuan perdata Notaris tersebut. Teori yang digunakan dalam menganalisa rumusan masalah apakah dengan tergabung dalam persekutuan perdata, Notaris tetap mempertahankan prinsip kemandirian dalam menjalankan jabatannya adalah dengan menggunakan teori pertanggung jawaban. Berdasarkan hasil pembahasan kemandirian Notaris terhadap akta yang dibuat dalam persekutuan perdata dapat dipertahankan karena tanggung jawab akta menjadi tanggung jawab Notaris yang membuat akta. Kemandirian Notaris tidak dapat dipertahankan karena menjalankan persekutuan perdata akan banyak melibatkan peran sekutu sehingga Notaris tidak mandiri terutama dalam finansial. Kata kunci: persekutuan perdata notaris, prinsip kemandirian notaris